Evaluation of the Implementation of Internal Control of Financial Reporting (ICOFR) on Maintenance Expenditure: Case Study of State Institution “X” - Fithriyyah Nur Afifah S; Dodik Siswantoro (Eduvest - Journal of Universal Studies, 2025)
This study evaluates the implementation of Internal Control over Financial Reporting (ICoFR) in maintenance expenditures at Government Institution X in Indonesia from 2019 to 2023. The objective is to assess the effectiveness of ICoFR, identify weaknesses in financial control, and propose improvements. This research employs a case study strategy with a qualitative descriptive approach. Data collection methods include semi-structured interviews, document analysis, and a review of audit reports from the Indonesian Supreme Audit Board (BPK). The research framework is based on the Minister of Finance Regulation No. 17/PMK.09/2019, which incorporates the COSO Internal Control Framework as its core reference. The findings indicate that ICoFR implementation in Government Institution X is not yet fully effective, as recurring audit findings highlight overpayments, contract discrepancies, and weak monitoring mechanisms. This study contributes to the literature by evaluating ICoFR implementation in a central government institution—an area that remains underexplored in academic research compared to corporate or local government financial reporting. The study also emphasizes the complex interplay of political and bureaucratic factors affecting financial control practices. Strengthening risk assessment, control activities, and compliance monitoring is crucial to improving transparency and accountability in maintenance expenditure management.